A biomechanical evaluation of different footrest heights during standing computer work. Issue 3 (4th March 2021) - Cregg, Andrew C.; Foley, Ryan C. A.; Livingston, Lori A.; La Delfa, Nicholas J.
Abstract: Working at a standing desk is a popular strategy to help reduce low back pain development during prolonged computer work. The purpose of this study was to examine how muscle activity, joint kinematics, weight distribution, balance and low back discomfort were affected by utilising footrests at different heights while working at a standing desk. Sixteen individuals performed a computer task at a standing workstation under four conditions: flat ground stance, and standing with one leg elevated on a low (10 cm), medium (20 cm), or high (30 cm) footrest. Footrest usage altered lumbo-pelvic and bilateral hip joint angles, muscle activity, weight distribution, and range of sway in the elevated limb. Additionally, footrest height altered lumbo-pelvic and hip joint position in the elevated limb. Discomfort increased with time across all conditions. Results suggest that intermittent utilisation of a footrest should be considered to promote changes in posture and muscle activity during prolonged computer use. Practitioner summary: This laboratory study showed that utilising a footrest between the heights of 10–30 cm during standing computer work may be beneficial to promote changes in posture and muscle activity over time. However, we recommend exercising caution while maintaining any standing position beyond 10 min of consecutive use. Abbreviations: LBP: low back pain; PD: pain developer; NPD: non-pain developer; GMe: gluteus medius; TFL: tensor fascia lata; LES: lumbar erector spinae; COP: centre of pressure; NDI: northern digital incorporated; CV: coefficient of variation; WHQ: waterloo handedness questionnaire; WFQ: waterloo footedness questionnaire; VAS: visual analogue scale; OBDI: Oswestry back disability index; IBS: International Society of Biomechanics; sEMG: surface electromyography; MVIC: maximum voluntary isometric contraction; RMS: root mean square; A/P: anterior/posterior; M/L: medial/lateral; % MVE: percentage of maximum voluntary excitation; ROM: range of motion; MCID: minimum clinically important difference